Phytochemical directed synthesis of flower-like ZnO nanostructures from almond peel extract for sunlight-activated congo red degradation - Sujesh Sudarsan; Jonas Van Caeneghem; Ramesh Vinayagam; Raja Selvaraj (PLoS ONE, 2026)
This study reports a low-temperature green route for producing sunlight-active zinc oxide (ZnO) nanoparticles using almond peel extract as the sole complexing and stabilizing medium and evaluates their performance toward Congo red (CR) removal from water. UV-visible analysis of the synthesized material shows a near UV absorption edge at 373 nm with an optical band gap energy of 3.32 eV. The photocatalyst possesses a mesoporous texture with a specific surface area of 31.89 m 2 /g and a mean pore diameter of 9.8 nm. FESEM reveals hierarchical flower-like assemblies composed of radially oriented ZnO rods, supported by EDS, confirming Zn and O as the dominant elements. XRD verifies phase-pure hexagonal wurtzite ZnO structures with a mean crystallite size of 39.24 nm. FTIR and XPS confirm ZnO formation and a phytochemical-derived surface overlayer containing hydroxyl, carbonyl, and aromatic functionalities, together with surface hydroxyls and chemisorbed oxygen. Photoluminescence indicates near-band-edge emission and defect-related visible bands consistent with oxygen vacancy and zinc-related trap states. Under natural sunlight (CR: 25 mg/L; catalyst dosage: 5–15 mg/100 mL; irradiation time 270 min), the material achieved 51.61 to 82.21% degradation and followed pseudo-first-order behaviour. Scavenger studies revealed that O 2 • − radicals are the dominant reactive species in dye degradation, with photogenerated h + playing a secondary role and •OH contributing minimally. Also, the ZnO nanoparticles exhibited good reusability, retaining over 83.64% of their initial photocatalytic activity after four cycles under sunlight irradiation. Thus, almond peel-derived ZnO offers a simple strategy to valorize an agricultural residue into a sunlight-responsive photocatalyst for treating dye-contaminated wastewater.